Reduced GLP-1R availability in the caudate nucleus with Alzheimer’s disease - Barrett, Emma; Ivey, Gabrielle; Cunningham, Adam; Coffman, Gary; Pemberton, Tyera; Lee, Chan; Patra, Prabir; Day, James B.; Lee, Peter H. U.; Shim, Joon W. (Frontiers in Aging Neuroscience, 2024)
The glucagon-like peptide-1 receptor (GLP-1R) agonists reduce glycated hemoglobin in patients with type 2 diabetes. Mounting evidence indicates that the potential of GLP1R agonists, mimicking a 30 amino acid ligand, GLP-1, extends to the treatment of neurodegenerative conditions, with a particular focus on Alzheimer's disease (AD). However, the mechanism that underlies regulation of GLP-1R availability in the brain with AD remains poorly understood.Here, using whole transcriptome RNA-Seq of the human postmortem caudate nucleus with AD and chronic hydrocephalus (CH) in the elderly, we found that GLP-1R and select mRNAs expressed in glucose dysmetabolism and dyslipidemia were significantly altered. Furthermore, we detected human RNA indicating a deficiency in doublecortin (DCX) levels and the presence of ferroptosis in the caudate nucleus impacted by AD. Using the genome data viewer, we assessed mutability of GLP-1R and 39 other genes by two factors associated with high mutation rates in chromosomes of four species. Surprisingly, we identified that nucleotide sizes of GLP1R transcript exceptionally differed in all four species of humans, chimpanzees, rats, and mice by up to 6-fold. Taken together, the protein network database analysis suggests that reduced GLP-1R in the aged human brain is associated with glucose dysmetabolism, ferroptosis, and reduced DCX+ neurons, that may contribute to AD.